1999
DOI: 10.1021/la980855d
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of the TiO2/Aqueous Solution Interface

Abstract: An innovative approach has been used to probe the molecular nature of the metal oxide/aqueous solution interface. Internal reflection spectroscopy of thin colloidal TiO2 films, under aqueous solutions of pH 11.7−2.3, has been used to obtain differential in situ infrared spectra related to interfacial species. An alkaline solution wash of the TiO2 films was shown to remove contaminants arising from the sol evaporation−film deposition process. Specific infrared absorptions have been assigned to terminal Ti−OH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
180
0
8

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(210 citation statements)
references
References 28 publications
22
180
0
8
Order By: Relevance
“…The estimated affinity constants explain the experimental PZC (Hiemstra et al, 1996b;Machesky et al, 2001) and also explain semi-quantitatively the in-situ IR absorption behavior observed by (Connor et al, 1999a) as discussed in Hiemstra and van Riemsdijk (2002).…”
Section: Resultssupporting
confidence: 78%
“…The estimated affinity constants explain the experimental PZC (Hiemstra et al, 1996b;Machesky et al, 2001) and also explain semi-quantitatively the in-situ IR absorption behavior observed by (Connor et al, 1999a) as discussed in Hiemstra and van Riemsdijk (2002).…”
Section: Resultssupporting
confidence: 78%
“…This reflects that the bridged group is more acidic than the terminal group according to the MUSIC model, and IR spectroscopy results independently support this contention (Connor et al, 1999). Uncomplexed Ti 2 O À0.555 sites decreased in abundance as pH increased primarily due to tetradentate and/or bidentate cation binding.…”
Section: Surface Speciationmentioning
confidence: 77%
“…[12][13][14] These broad bands are observed in IE-911 (binder plus CST), acid and NaOH-treated forms. In IE-910, the bands of the Si-Ti-Nb-O CST framework below 1200 cm -1 are relatively sharp, since CST is a crystalline (ordered) material.…”
Section: Binder Characterization Studiesmentioning
confidence: 97%